2016
DOI: 10.5539/ijms.v8n2p138
|View full text |Cite
|
Sign up to set email alerts
|

Internet Motives of Users in Jordan, UAE and KSA: A Cross-Cultural Validation of the Web Motivation Inventory (WMI)

Abstract: The aim of this study is to replicate the Web Motivation Inventory (WMI) in new context. To date, the scale has only been tested on consumers in the United States, United Kingdom, Australia and South Korea. This research replicates the WMI using consumers from three Arab countries namely Jordan, UAE, and KSA. Results show that the same four-factor structure has been produced for the three countries, providing evidence of the scales cross cultural stability. Additional results show that there were differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The small number of customers who reported that they did not have access to the internet is supported by the fact that 86.1 percent of the population in Jordan has internet access (Khraim, 2016).…”
Section: Response Ratementioning
confidence: 99%
“…The small number of customers who reported that they did not have access to the internet is supported by the fact that 86.1 percent of the population in Jordan has internet access (Khraim, 2016).…”
Section: Response Ratementioning
confidence: 99%
“…A report in 2012 found that children and adolescents in Australia spent nearly 24 h online per month with persons 18–24 years of age spending an average of 65 h online and individuals 25–34 years of age spending more than 100 h per month (Affouneh et al 2021 ). In the Arab world, there are roughly around 135 million Internet users, with these staggering numbers it is evident that problematic internet use has emerged as a global concern (Khraim, 2016 ; Kuss et al 2014 ; Poli, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Islamic religion also affects consumer behaviour, ethical beliefs, and conduct (Abou-Youssef, Kortam, Abou-Aish, & El-Bassiouny, 2011). Religion plays a vital role in social interactions and consumer behaviour (Khraim, 2016).…”
Section: Religion and Religiositymentioning
confidence: 99%
“…Islamic religion also affects consumer behaviour, ethical beliefs, and conduct (Abou-Youssef et al, 2011). Religion plays a vital role in social interactions and consumer behaviour (Khraim, 2016), especially in Arab/Islamic cultures where religiosity plays a vital role in consumer behaviour (Al-Hyari et al, 2012). George (1987) held that religion is a primary force in business ethics.…”
Section: Religiositymentioning
confidence: 99%
See 1 more Smart Citation